Bread waste valorization: a review of sustainability aspects and challenges - Hafyan, Rendra Hakim; Mohanarajan, Jasmithaa; Uppal, Manaal; Kumar, Vinod; Narisetty, Vivek; Maity, Sunil K.; Sadhukhan, Jhuma; Gadkari, Siddharth (Frontiers in Sustainable Food Systems, 2024)
Bread waste (BW) poses a significant environmental and economic challenge in the United Kingdom (UK), where an estimated 20 million slices of bread are wasted daily. BW contains polysaccharides with great potential for its valorization into building block chemicals. While BW valorization holds tremendous promise, it is an emerging field with low technology readiness levels (TRLs), necessitating careful consideration of sustainability and commercial-scale utilization. This review offers a comprehensive assessment of the sustainability aspects of BW valorization, encompassing economic, environmental, and social factors. The primary objective of this review article is to enhance our understanding of the potential benefits and challenges associated with this approach. Incorporating circular bioeconomy principles into BW valorization is crucial for addressing global issues stemming from food waste and environmental degradation. The review investigates the role of BW-based biorefineries in promoting the circular bioeconomy concept. This study concludes by discussing the challenges and opportunities of BW valorization and waste reduction, along with proposing potential strategies to tackle these challenges.